PC Deficiency Testing: Thrombin-Thrombomodulin as PC Activator and Aptamer-Based Enzyme Capturing Increase Diagnostic Accuracy - Reda, Sara; Rühl, Heiko; Witkowski, Jana; Müller, Jens; Pavlova, Anna; Oldenburg, Johannes; Pötzsch, Bernd (Frontiers in Cardiovascular Medicine, 2021)
Protein C (PC) activity tests are routinely performed in a thrombophilia workup to screen for PC deficiency. Currently used tests combine conversion of PC to activated PC (APC) by the snake venom Protac with subsequent APC detection through hydrolysis of a chromogenic peptide substrate or prolongation of a clotting time. In this prospective cohort study, we analyzed how different modes of PC activation and subsequent APC determination influence the diagnostic accuracy of PC activity testing in a cohort of 31 patients with genetically confirmed PC deficiency. In addition to chromogenic and clot-based measurement, an oligonucleotide-based enzyme capture assay utilizing a basic exosite-targeting aptamer was used for APC detection. To study the influence of the PC activation step on diagnostic sensitivity, PC activation through Protac and through the thrombin-thrombomodulin (TM) complex were compared. Twenty-six (84%) and 24 (77%) PC deficient patients were identified as true-positive using the chromogenic and the clot-based PC activity assay, respectively. True-positive results increased to 27 (87%) when the basic exosite-targeting aptamer approach was used for APC measurement. Additional replacement of the PC activator Protac by thrombin-TM gave true-positive results in all patients. These data indicate that the mode of PC activation is crucial in determining the accuracy of PC activity testing and that diagnostic sensitivity can be significantly improved by replacing the PC activator Protac with thrombin-TM. APC detection using a basic exosite-targeting aptamer achieves high sensitivity towards mutations outside the active center while being less subject to interfering factors than clot-based PC activity assays.